CITRA POSITIF LAKI-LAKI BATAK DALAM FILM NGERI-NGERI SEDAP (Analisis Semiotika Roland Barthes) - Sagala, Ronal Arpandi; Hasan, Kamaruddin (Prodi Ilmu Komunikasi, 2024)
In the mass media industry, films can perpetuate stereotypes about certain ethnic groups. For example, the Batak tribe is often described as a tough and strict tribe, especially towards men. The film 'Ngeri-Ngeri Sedap' released in 2022 is the latest example of this, depicting family conflict in a Batak family. This research analyzes the film 'Ngeri-Ngeri Sedap' using Roland Barthes' semiotic analysis, focusing on aspects of Denotation, Connotation and Myth. Other important values are Hamoraon (wealth), Hagabeon (offspring), and Hasangapon (honor). The film